The Relationship between Contextual ESG Reporting and Green Supply Chain Accounting on Cost Efficiency and Credit Assessment in MSMEs in West Java - Puspa, Eka Septariana; Muhtadi, Muhamad Ammar; Novitasari, Salwa Aulia (West Science Social and Humanities Studies, 2025)
This study investigates the influence of contextual Environmental, Social, and Governance (ESG) reporting and green supply chain accounting on cost efficiency and credit assessment of Micro, Small, and Medium Enterprises (MSMEs) in West Java. Using a quantitative research design, data were collected from 250 MSME respondents through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) 3. The findings indicate that contextual ESG reporting and green supply chain accounting significantly enhance cost efficiency by reducing operational waste and optimizing resource use. Both variables also positively influence credit assessment, reflecting the growing recognition by financial institutions of sustainable business practices as indicators of financial credibility and resilience. These results highlight the dual benefits of sustainability practices, providing MSMEs with internal efficiency gains and external access to financing opportunities. The study contributes to the literature by emphasizing the relevance of ESG and green supply chain practices for MSMEs in emerging economies, offering both theoretical insights and practical implications for policymakers, business owners, and financial institutions in supporting sustainable economic development.